2019
DOI: 10.1002/nau.23919
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term treatment of older patients with overactive bladder using a combination of mirabegron and solifenacin: a prespecified analysis from the randomized, phase III SYNERGY II study

Abstract: AimsSYNERGY II was a 12‐month phase III trial in patients with overactive bladder (OAB) symptoms that investigated the safety and efficacy of the combination of mirabegron and solifenacin in comparison with each monotherapy. This analysis evaluated the trial findings using four age subgroups (<65, ≥65, <75, and ≥75 years).MethodsEligible patients were ≥18 years with symptoms of “wet” OAB (urinary frequency and urgency with incontinence) for ≥3 months. Patients were randomized to receive once‐daily solifenacin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Our study showed that PVR was significantly increased in the solifenacin‐added‐on and mirabegron‐added‐on groups, but no severe adverse events, such as acute urinary retention, was noted. This finding was similar to several solifenacin and mirabegron studies, which showed that a statistically significant increase of PVR was noted in the study group, but an elevated PVR did not increase severe adverse events 2,4 …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our study showed that PVR was significantly increased in the solifenacin‐added‐on and mirabegron‐added‐on groups, but no severe adverse events, such as acute urinary retention, was noted. This finding was similar to several solifenacin and mirabegron studies, which showed that a statistically significant increase of PVR was noted in the study group, but an elevated PVR did not increase severe adverse events 2,4 …”
Section: Discussionsupporting
confidence: 90%
“…Patients were randomly assigned to receive treatment with solifenacin 5 mg QD (solifenacin add‐on, 30 patients), mirabegron 50 mg QD (mirabegron add‐on, 31 patients), or no medication (BoNT‐A only, 29 patients). We chose the same dose of solifenacin 5 mg and mirabegron 50 mg as the previous phase III SYNERGY study 4 . The randomization was performed using a computer‐generated randomization scheme (Cenduit GmBH, Allschwil, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Over and above, to get higher effectiveness without increasing side effects mirabegron was combined with solifenacin. 25 Improved QoL and prolonged time to micturition were the essential parametres of our study outcomes. Besides, combination was better than other treatment modalities.…”
Section: Discussionmentioning
confidence: 81%
“…Mirabegron, alone or in combination with solifenacin, is also a well tolerated and effective treatment for patients with overactive bladder (OAB) symptoms, irrespective of their age. 15 …”
Section: Introductionmentioning
confidence: 99%